Costo de producción en la cría y manejo de pollos broiler en la granja DIALMAS del Cantón La Maná, Provincia de Cotopaxi, año 2020 - Ayala Chiguano, Jessica Alexandra (2022)
This research project aims to determine the cost of production in the breeding and handling of broiler chickens, in the DIALMAS Farm, San Pedro Enclosure, La Maná Canton, Cotopaxi Province, since the main problem of the DIALMAS farm is that it does not have a correct management with respect to its real production costs. The research methodology used was the field research in the Farm Facilities, the methods used were: the inductive, deductive, in addition to the technique of the interview applied to the owner manager and survey to his workers, through which the pertinent information was obtained regarding the production process of broiler chickens that ranges from the preparation of sheds, reception of chickens, breeding and sale. The cost determination yielded a value of $15,044.00 of the direct raw material, $255.00 with respect to direct labor, $433.00 of indirect raw material, $120.00 of indirect labor and indirect manufacturing costs reflected a value of $353.02 giving a total of $16,205.02 of the production costs. While the income generated by the sale of 3880 chickens and tamos gave a value of $ 19,913.00, and a net profit of $ 1,844.88, during the first production of the year 2020 in the DIALMAS Farm.